2013
DOI: 10.7454/jki.v16i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Perawat Tentang Terapi Infus Mempengaruhi Kejadian Plebitis dan Kenyamanan Pasien

Abstract: Plebitis adalah salah satu komplikasi terapi infus. Salah satu faktor penyebab plebitis adalah kurang terampilnya perawat saat melakukan pemasangan infus. Tujuan penelitian adalah mengetahui hubungan pengetahuan perawat tentang terapi infus dengan kejadian plebitis dan kenyamanan. Jenis penelitian analitic-corelational dengan pendekatan cross-sectional, dengan jumlah sampel 65 perawat pelaksana rawat inap dan 65 pasien yang dipasang infus. Hasil menunjukkan 50,8% perawat memiliki pengetahuan kurang baik, angka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
7
0
10
Order By: Relevance
“… 20 Studies have also demonstrated that there is a significant correlation between nurses’ knowledge about infusion therapy and phlebitis incidences. 14 In contrast, a study on neonates in New Zealand stated that the discipline of the inserter might not be the factor causing the peripheral intravenous complication. 21 It is necessary to consider the clinical experience of the nurses in resolving the peripheral infusion cases in LBW.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 20 Studies have also demonstrated that there is a significant correlation between nurses’ knowledge about infusion therapy and phlebitis incidences. 14 In contrast, a study on neonates in New Zealand stated that the discipline of the inserter might not be the factor causing the peripheral intravenous complication. 21 It is necessary to consider the clinical experience of the nurses in resolving the peripheral infusion cases in LBW.…”
Section: Discussionmentioning
confidence: 97%
“…Infusion Nurses Society suggests that the rate of phlebitis should be equal to or less than 5%. 14 Among the complications resulting from infusion insertion, 17.84%-77.5% were phlebitis. 7 , 15 Similar studies on pediatrics showed that phlebitis incidences ranged from 9%-71.25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angka kejadian plebitis di RSUD Indramayu masih di atas standar INS. Sementara kejadian plebitis yang dilaporkan tersebut adalah plebitis sudah tahap lanjut (Wayunah, 2011). Angka kejadian plebitis yang direkomendasikan oleh Infusions Nurses Society adalah 5%.…”
Section: Menurut Infusion Nursing Societyunclassified
“…The significant risk factors that contributed to the high incidence were dwelling time, infusate type, and gender. In Indonesia, the incidence rate of phlebitis was 40%, and a relationship between nurses' knowledge about infusion therapy and phlebitis percentage was found (Wayunah et al, 2013). A study in South Korea identified four significant predictive factors (six categories) of PIVC-related phlebitis for orthopedic patients, namely, vein quality, contrast agent use, hand hygiene, and nursing experience (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%